PILE FOUNDATION AND EARTH RETAINING STRUCTURE DESIGN OF HOTEL AND CONVENTION CENTER PROJECT AT KUNINGAN, JAKARTA - Wiranto
The project studied in this design thesis is a hotel and convention center building which is planned in Kuningan, Jakarta. The building consists of a tower side and a podium side where the tower side consists of x floors and the podium side consists of y floors, and under both sides are 2 basement floors. From the building, the substructure side related to geotechnical engineering will be designed in this thesis. To realize the basement side of the building, excavation needs to be carried out, where the lateral soil pressure needs to be restrained by a retaining structure in the form of a diaphragm wall with a supporting structure in the form of a ground anchor. Analysis of the retaining structure is based on Rankine's theory of lateral earth pressure in undrained soil conditions, where the overturning moment and the holding moment from lateral earth pressure are compared to obtain the required ground anchor dimensions. The design results obtained are then modeled on the Plaxis 2D software, to obtain results that are difficult to obtain with manual calculations. Besides the retaining structure, a building foundation is also designed to carry the load from the superstructure. The foundation used is a group piles foundation with driven piles. Foundation analysis includes bearing capacity and settlement analysis. The axial bearing capacity is analyzed with manual calculations based on the equations from research results that are often used in Indonesia, while the lateral bearing capacity is analyzed by the Group Pile software. Settlement is estimated by manual calculations, which is then compared with the results from the Plaxis 3D software.